CITRA DESTINASI WISATA SUKU BADUY DAN DAMPAKNYA TERHADAP KUNJUNGAN WISATA PASCA PANDEMI COVID 19 - Yuli Harwani; Dudi Permana; Yanto Ramli; Eka Prasetiawan (Universitas Mercu Buana, 2023)
Covid-19 is a global pandemic that affects all sectors including the tourism sector. Almost all tourist destinations are affected. This study aims to determine and examine the impact of the image of the Baduy Tribe tourist destination on tourist visits after the Covid-19 Pandemic. The research method uses a qualitative-descriptive method. The subjects used are tourists who have visited the village of the Baduy Tribe. The analysis technique used is explanatory. The results of the study show that the image of the Baduy Tribe tourist destination has an impact on tourist visits after the Covid-19 Pandemic. It is recommended that efforts be made to attract tourists for return visits to the Baduy Tribe.